Local Weather Effects: Perception of Climate Change and Public Support for Government Intervention. (18th February 2021) - Kim, Jeong Hyun; Seo, Min Hee; Sinclair, Betsy
Abstract : Objective: This article examines how people's lived experience of local weather might influence climate policy preferences in the presence of strong partisan bias. Methods: Using a comprehensive dataset combining four‐wave panel survey responses from U.S. residents over three years with geocoded data on their local weather experience, we evaluate the impacts of local weather variations on beliefs about climate change, risk perceptions of climate change, and climate policy preferences. The panel structure of our data allows us to causally identify how one's actual experience of weather modifies climate change opinions over time. Results: We find that both long‐ and short‐term unusual local weather experiences change individuals' climate change opinions and preferences on climate change policy. Conclusion: One's lived experience alters beliefs in climate change, risk perceptions of climate change, and preferences for government climate policy even in the context of strong partisan bias.